Volatility Spillover between the IDR-USD Exchange Rate and Sectoral Stock Indices using EGARCH Model - Putri Zahra Helena; Dwi Susanti; Budi Nurani Ruchjana (International Journal of Quantitative Research and Modeling, 2025)
The exchange rate is an important indicator in an open economy such as Indonesia, where fluctuations in currency values, particularly the USD against the IDR, have a significant impact on the Indonesian financial market. Sectoral stock indices, as one of the components of the financial market, reflect the specific financial conditions of each sector in Indonesia. The USD, as the dominant global currency, influences various sectors, especially those related to foreign exchange transactions. The relationship between exchange rates and sectoral stock indices may indicate interdependence in volatility or the presence of volatility spillover effects. Therefore, this study aims to identify the presence of volatility spillover between the IDR-USD exchange rate and three sectoral stock indices in Indonesia, namely the financial sector (JKFINANCE), the energy sector (JKENERGY), and the infrastructure sector (JKINFRA). The Exponential Generalized Autoregressive Conditional Heteroscedasticity (EGARCH) model is used to capture asymmetric volatility. Based on the estimation results, the best-fitting EGARCH models are EGARCH(2,3) for the IDR-USD exchange rate, EGARCH(3,1) for the financial sector, EGARCH(2,4) for the energy sector, and EGARCH(2,5) for the infrastructure sector. The γ parameters from these models indicate that bad news increases volatility in the exchange rate, financial sector, and energy sector, while good news has a greater impact on volatility in the infrastructure sector. Furthermore, Granger Causality tests on the residuals of the EGARCH models reveal the existence of volatility spillovers between the IDR-USD exchange rate and the financial, energy, and infrastructure sector.